Anak-anak dan Advergame: Pengaruh Pengalaman Flow dan Persuasion Knowledge pada Sikap dan Niat Pembelian - Santirianingrum Soebandhi; Sri Hartini; Sri Gunawan (Faculty of Economics and Business Udayana University, 2020)
Playing a video game has become a favorite activity for children. One of the marketing efforts to attract their attention is by combining advertising and entertainment in the form of advergame or advertising game. Childhood is considered as a critical period towards the impact of advertising. As more advergame played especially intended for children, this study aims to analyze the effectiveness of advergame through flow experience and persuasion knowledge towards advergame and brand attitude as well as their purchase intention towards the embedded product in the game. This study was participated by 218 children aged 10-12 years old in Jakarta and Surabaya. Seven hypotheses were proposed to be analyzed further. Different from the previous studies, this study shows that attitudes on advergame do not influence the children intention to purchase the advertised product. The findings also offer some implications, limitations and directions to the future research.